BRUCELLA SPONDYLITIS IN A MARRIED COUPLE - Ajda Bal,; Eda Gürçay,; Emel Ekşioğlu,; Tahsin Edgüer,; Reyhan Tuncay,; Aytül Çakcı, (Archives of Rheumatology, 2003)
The frequency of brucella spondylitis has been reported to be of 9.1-58 %, in cases with brucella infection, involving the lumbar segment most frequently. Paravertal abscess is reported 16% of the cases. In this report, two simultaneous spondylitis cases secondary to Brucellosis in a married couple have been investigated. Both cases underwent medical treatment for brucellosis. Clinical, laboratory and Magnetic Resonance Imaging findings were found to be improved 10 months later. In conclusion, brucellosis may cause spondylitis and its attendant neurological complications. The possibility of more than one cases in the same family should always be kept in mind. The disease can be cured with proper treatment.